2021
DOI: 10.3389/fped.2021.595882
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Postnatal Growth Charts of Singleton Preterm and Term Infants Using World Health Organization Standards at 40–160 Weeks Postmenstrual Age: A Chinese Single-Center Retrospective Cohort Study

Abstract: There remains controversy regarding whether the growth charts constructed from data of term infants, such as those produced by the World Health Organization (WHO) standards, can appropriately evaluate the postnatal growth of preterm infants. This retrospective cohort study, conducted in the First Affiliated Hospital of Shandong First Medical University in Jinan China, aimed to compare the postnatal growth charts of singleton preterm and term infants using WHO standards at 40–160 weeks postmenstrual age (PMA). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…During the rst year of age, there were signi cant differences in the growth rates of length and weight of preterm and full-term infants at different stages. The growth rates of preterm infants were signi cantly lower than those of full-term infants from birth to 3 months, and gradually caught up to the level of fullterm infants after 3 months [20]. Speci cally, the growth rates of preterm and full-term infants were attributed to the regulatory mechanism of growth hormone (GH), insulin-like growth factor-1 (IGF-1), and insulin-like growth factor binding protein-3 (IGFBP-3).…”
Section: Discussionmentioning
confidence: 91%
“…During the rst year of age, there were signi cant differences in the growth rates of length and weight of preterm and full-term infants at different stages. The growth rates of preterm infants were signi cantly lower than those of full-term infants from birth to 3 months, and gradually caught up to the level of fullterm infants after 3 months [20]. Speci cally, the growth rates of preterm and full-term infants were attributed to the regulatory mechanism of growth hormone (GH), insulin-like growth factor-1 (IGF-1), and insulin-like growth factor binding protein-3 (IGFBP-3).…”
Section: Discussionmentioning
confidence: 91%
“…Nevertheless, whether the actual postnatal growth of a specific preterm population differs from that of the IPPGS determines the interpretation of the growth assessment results with the IPPGS and subsequent clinical decisions, such as the optimal time point to terminate fortified nutrition. In addition, our previous studies demonstrated higher growth levels among preterm infants in Shandong, China, than those indicated by the Fenton reference and WHO standards before the corrected age of 2 years old ( 22 , 23 ). Therefore, we hypothesized that this preterm population might also have higher postnatal growth levels than those of the IPPGS.…”
Section: Introductionmentioning
confidence: 77%
“…Recently, emerging studies have proposed that disparities exist in growth between specific preterm populations and international growth standards/references. For example, our previous study proved that singleton preterm infants had higher growth levels than that of WHO standards but had similar growth levels to term infants in the same center from corrected term to 2 years of age ( 23 ). A multicenter cohort study conducted in Sichuan, China, demonstrated that preterm infants had higher growth levels than those of the IPPGS and WHO standards and had consistent growth with their term counterparts after 3 months of corrected age ( 21 ).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…[20] During the first year of life, there were significant differences in the growth rates of the length and weight of preterm and full-term infants at different stages. [21] Specifically, the growth rates of preterm and full-term infants have been attributed to the regulatory mechanism of growth hormone, insulin-like growth factor-1 (IGF-1), and insulin-like growth factor binding protein-3 (IGFBP-3). As for the regulatory mechanism, growth hormone was an important regulator for the growth rates of preterm infants in a pulsed pattern, and IGF-1 formed a complex with IGFBP-3 which was closely related to the growth rates of preterm infants.…”
Section: Discussionmentioning
confidence: 99%